Revelation is Unlimited: Divinely Inspired Speeches, “Testing” and the Spiritual Training in the Subud Movement - Widiyanto, Asfa (Universitas Negeri Semarang, 2016)
The Subud Movement is one of the mystical movements which develop in the Indonesian archipelago. This movement originated from the spiritual experience of its founder, Muhammad Subuh Sumahadiwidjojo (1901-1987), in 1925. This paper is devoted to highlighting the nature of revelation in the Subud Movement. I will show that revelation is not a taboo in the movement and even becomes the legitimacy of leadership, in particular for the founder of the Movement. This can be observed most notably from the existence of divinely inspired talks, “testing” and the latihan kejiwaan (spiritual training) in the movement. In order to grasp more readily the nature of revelation in the Subud Movement, I also provide an overview of the discourse of leadership and revelation in Javanese mystical tradition.